Perancangan Ulang UI/UX Website Pinus Banyuwangi menggunakan Metode Human Centered Design - Kholifatul Putri, Siti Nur; Khoirul Umam; Dimyati Ayatullah; Lutfi Hakim; Devit Suwardiyanto (Jurnal Informatika dan Komputer, 2024)
With the advancement of information technology, websites have become essential platforms for disseminating information and advertising products and services online. A website is considered good when it strikes a balance between visual appeal and usability. However, the graphics on the Pinus Banyuwangi website still appear rigid and monotonous, and the information is poorly organized, leading users to struggle in understanding the services offered. To ensure users can truly experience Pinus Banyuwangi and its services, the website's interface and user experience need to be redesigned, taking into account user experience through the Human-Centered Design approach, which involves four stages Observation, Idea Generation, Prototype, and Testing. The research indicates significant user concerns regarding the UI and UX of the Pinus Banyuwangi website. Through questionnaires and final testing using a system usability scale method involving 30 Banyuwangi Pines visitors, the obtained score of 79.2 corresponds to a B value indicator, signifying an acceptable level of usability. This demonstrates an improvement in usability compared to the initial testing score of 32, which fell under the "F Unacceptable“ category. The research results culminate in the creation of a UI/UX prototype for the Pinus Banyuwangi website, aiming to be user-friendly and tailored to user needs.